Bridging Regulatory Diversity: Halal Certification Frameworks in Indonesia, Malaysia, and Singapore and the Road to ASEAN Harmonisation - Sudi, Didih Muhamad (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2025)
With the growing significance of halal product assurance in ASEAN, the demand for regulatory harmonisation is alarming with the phenomenon of globalization. This study attempts to analyse and compare the regulatory frameworks of halal product assurance from countries in ASEAN to find similarities and differences and aspects that require development. In this study, a comparative method was used to compare the legal and policies of the halal product assurance in Indonesia, Malaysia and Singapore. This study demonstrates that mandatory certification under Indonesian JPH law does ensure comprehensive regulation but impedes several industry sizes as well as intricacies during implementation. In Malaysia, JAKIM has established a known voluntary scheme all over the globe. Its governance system is excellent and has enabled Malaysia to lead the halal market globally. On the other hand, Singapore's model is highly regulated and overseen by MUIS. It serves the global economy while ensuring strict halal standards. The differences in regulations should be harmonised as they could otherwise translate into trade barriers besides affecting consumer confidence. A more integrated, competitive, and visible halal industry in the ASEAN global market can be achieved by harmonising such differences through policy alignments, coordination among agencies, and technological utilisation